Optimalisasi Lubang Resapan Biopori dalam Mendukung Ketahanan Lingkungan di Desa Singajaya Melalui Program KKN: Pengabdian - Fikfik Taufik; Farid Fahrezi; Camelia Dwiyanti Prasetya; Indri Oktaviani; Michael Satrio Ibrahim; Nadia Azzahra Fadhilah; Mohammad Faisal Asssyiq; Monica Julieta; Nela Sopiani; Regita Cahyani Maulana; Indallah Mazaya Salamah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Community Service Program (KKN) is a curriculum program that gives students the opportunity to apply knowledge, think critically, and gain practical experience within the community. The KKN program in Singajaya Village, West Bandung Regency, was conducted to address environmental issues, particularly regarding organic waste management and waterlogging. Initial observations revealed that the community did not fully understand the benefits and application of biopore infiltration holes. Using a qualitative method, students from Universitas Muhammadiyah Bandung conducted a socialization and implementation of biopore infiltration holes (LRB) as a simple, economical, and environmentally friendly solution. As a result, the program successfully increased community awareness about organic waste management. LRB was proven effective in converting waste into compost, reducing waste accumulation, and preventing waterlogging, which in the long run can help prevent flooding. The program received a positive response, and the community hopes that LRB can be more widely implemented to ensure environmental sustainability in the village.